Transformational and Transactional Leadership in Semi-Military Organizations: Their Differential Impact on Work Engagement - Sipahelut, Semuel Willem; Wokanubun, Paulina; Para, Rudolf; Maranressy, Kristina (Jurnal Aplikasi Manajemen, 2025)
In hierarchical and high-control environments such as correctional institutions, leadership style plays a crucial role in shaping work engagement. However, limited empirical research in semi-militarized contexts, particularly in correctional facilities with rigid structures and strict discipline, still leaves a significant gap in understanding leadership. This study aims to examine whether transformational and transactional leadership styles influence work engagement within a semi-militarized organizational setting, specifically, the Class IIA Correctional Institution in Ambon. Data were collected through a census questionnaire distributed to 90 employees and analyzed using multiple regression with the assistance of SPSS 16 for Windows. The findings indicate that both transformational and transactional leadership styles have a significant joint effect on work engagement. However, when examined individually, only transformational leadership demonstrates a significant influence, while transactional leadership shows no meaningful impact. Moreover, transformational leadership exhibits a moderate and significant correlation with the dimensions of absorption and dedication, and a low but significant correlation with vigor. In contrast, transactional leadership demonstrates a very low and statistically insignificant correlation with all three dimensions of work engagement. This study contributes novel empirical insights from a rarely examined semi-militarized context. These findings have significant practical implications for leadership development in highly regulated, discipline-intensive environments, highlighting the strategic advantage of transformational approaches in fostering motivation, dedication, and overall organizational effectiveness.